Comparison of Oncological Outcomes Between Radical Prostatectomy and Radiotherapy by Type of Radiotherapy in Elderly Prostate Cancer Patients - Guo, Xiao-Xiao; Xia, Hao-Ran; Hou, Hui-Min; Liu, Ming; Wang, Jian-Ye (Frontiers in Oncology, 2021)
Objective: We aimed compare the oncologic outcomes of radical prostatectomy (RP) with those of external beam radiotherapy (EBRT), brachytherapy (BT), or EBRT + BT (EBBT) in elderly patients with localised prostate cancer (PCa). Methods: Localised PCa patients aged ≥70 years who underwent RP, EBRT, BT, or EBBT between 2004 and 2016 were identified from the Surveillance, Epidemiology, and End Results database. Multivariable competing risks survival analyses were used to estimate prostate cancer-specific mortality (CSM) and other-cause mortality (OCM). Subgroup analyses according to risk categories were also conducted. Results: Overall, 14057, 37712, 8383, and 5244 patients aged ≥70 years and treated with RP, EBRT, BT, and EBBT, respectively, were identified. In low-to-intermediate-risk patients, there was no significant difference in CSM risk between RP and the other three radiotherapy modalities (all P > 0.05). The corresponding 10-year CSM rates for these patients were 1.2%, 2.3%, 2.0%, and 1.8%, respectively. In high-risk patients, EBRT was associated with a higher CSM than RP (P = 0.003), whereas there was no significant difference between RP and BT or RP and EBBT (all P > 0.05). The 10-year CSM rates of high-risk patients in the RP, EBRT, BT, and EBBT groups were 7.5%, 10.2%, 8.3%, and 7.6%, respectively. Regarding OCM, the risk was generally lower in RP than in the other three radiotherapy modalities (all P < 0.001). Conclusions: Among men aged ≥70 years with localised PCa, EBRT, BT, and EBBT offer cancer-specific outcomes similar to those of RP for individuals with low-to-intermediate-risk disease. In patients with high-risk disease, EBBT had outcomes equally favourable to those of RP, but RP is more beneficial than EBRT. More high-quality trials are warranted to confirm and expand the present findings.